2010
DOI: 10.1007/s00198-010-1458-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in calcaneal quantitative ultrasound measures during childhood

Abstract: Summary This longitudinal study examined how calcaneal quantitative ultrasound (QUS) measures change during childhood while taking into account skeletal maturation, body mass index (BMI), and physical activity. The study reported sex differences in QUS growth curves and an inverse relationship between BMI and speed of sound (SOS) measures. Introduction The aim of this study was to examine how calcaneal QUS parameters change over time during childhood and to determine what factors influence these changes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
(107 reference statements)
1
4
1
Order By: Relevance
“…While BUA is a measure of how the ultrasound signal is absorbed or scattered by the bone and therefore reflects its porosity (density) without taking into account the surrounding soft tissue23. In healthy girls, BUA has been shown to increase with age2324 while data for AD-SOS is less consistent with one study showing an increase24, and another no change23. In our cohort of TS patients BMD did not alter with age, AD-SOS decreased and BUA increased.…”
Section: Discussioncontrasting
confidence: 50%
“…While BUA is a measure of how the ultrasound signal is absorbed or scattered by the bone and therefore reflects its porosity (density) without taking into account the surrounding soft tissue23. In healthy girls, BUA has been shown to increase with age2324 while data for AD-SOS is less consistent with one study showing an increase24, and another no change23. In our cohort of TS patients BMD did not alter with age, AD-SOS decreased and BUA increased.…”
Section: Discussioncontrasting
confidence: 50%
“…Age and BMI were good predictors of BUA and BQI values in our linear regression model. These results are consistent with some studies (8,9). A previous study reported that overweight prepubertal boys had better DEXA bone parameters than that of boys with normal nutritional status (24).…”
Section: Anthropometry and Qussupporting
confidence: 92%
“…The beneficial effects of exercise on skeletal health is evident (5)(6)(7). Bone parameters are also associated with age, several anthropometric variables and body fat percentage (8,9). Some previous studies have focused on the relationship between calcium and vitamin D intake and bone properties, and the effect of calcium supplementation on bone health during the prepubertal years (2,9).…”
Section: Introductionmentioning
confidence: 99%
“…QUS, measuring the attenuation and velocity of ultrasound waves passing through the calcaneus bone, is now part of bone health assessment [28]. It has been reported that Broadband Ultrasound Attenuation (BUA) and Speed of Sound (SOS) exhibit distinct structural properties of bone, with BUA more related to structural parameters such as connectivity and porosity of the skeleton, and SOS more influenced by bone mineral mass and elasticity [29].…”
Section: Submit Your Manuscript | Wwwaustinpublishinggroupcommentioning
confidence: 99%